Does a neutral thermal sensation determine thermal comfort?. (March 2018) - Shahzad, Sally; Brennan, John; Theodossopoulos, Dimitris; Calautit, John K; Hughes, Ben R
The neutral thermal sensation (neither cold, nor hot) is widely used through the application of the ASHRAE seven-point thermal sensation scale to assess thermal comfort. This study investigated the application of the neutral thermal sensation and it questions the reliability of any study that solely relies on neutral thermal sensation. Although thermal-neutrality has already been questioned, still most thermal comfort studies only use this measure to assess thermal comfort of the occupants. In this study, the connection of the occupant's thermal comfort with thermal-neutrality was investigated in two separate contexts of Norwegian and British offices. Overall, the thermal environment of four office buildings was evaluated and 313 responses (three times a day) to thermal sensation, thermal preference, comfort, and satisfaction were recorded. The results suggested that 36% of the occupants did not want to feel neutral and they considered thermal sensations other than neutral as their comfort condition. Also, in order to feel comfortable, respondents reported wanting to feel different thermal sensations at different times of the day suggesting that occupant desire for thermal comfort conditions may not be as steady as anticipated. This study recommends that other measures are required to assess human thermal comfort, such as thermal preference. Practical application: This study questions the application of neutral thermal sensation as the measure of thermal comfort. The findings indicate that occupant may consider other sensations than neutral as comfortable. This finding directly questions the standard comfort zone (e.g. ASHRAE Standard 55) as well as the optimum temperature, as many occupants required different thermal sensations at different times of the day to feel comfortable. These findings suggest that a steady indoor thermal environment does not guarantee thermal comfort and variations in the room temperature, which can be controlled by the occupant, need to be considered as part of the building design.